2006
DOI: 10.1051/fruits:2006013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combined inoculation of arbuscular mycorrhizal fungi and plant growth-promoting rhizobacteria on papaya (Carica papayaL.) infected with the root-knot nematodeMeloidogyne incognita

Abstract: Effect of the combined inoculation of arbuscular mycorrhizal fungi and plant growth-promoting rhizobacteria on papaya (Carica papaya L.) infected with the root-knot nematode Meloidogyne incognita.Abstract --Introduction. Arbuscular mycorrhizal fungi (AMF) and plant growth-promoting rhizobacteria (PGPR) can be considered important rhizospheric beneficial microorganisms. Their use as biocontrol strategies against soilborne pathogens such as nematodes should be taken into account. However, optimal management of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(12 citation statements)
references
References 30 publications
1
9
0
2
Order By: Relevance
“…Since AM fungi and RKN are all indigenous soil organisms and therefore co-exist in plant roots, the potential role of AM fungi as biocontrol agents and their protective effects on plants against RKN have been well documented Diedhiou et al 2003). Studies have shown that inoculation with AM fungi can significantly reduce RKN infestation and reproduction in some plant-nematode systems (Hol and Cook 2005) such as papaya with Meloidogyne incognita (Jaizme- Vega et al 2006), olive planting stocks with M. incognita and Meloidogyne javanica (Castillo et al 2006), tomato with M. incognita (Talavera et al 2001;Siddiqui and Akhtar 2007), pyrethrum with Meloidogyne hapla (Waceke et al 2001), Prunus rootstocks with M. javanica (Calvet et al 2001), and banana with M. javanica (Rodriguez and JaizmeVega 2005). In addition to enhancement of plant nutrition, especially P nutrition, establishment of arbuscular mycorrhizae may exert beneficial effects on plant growth though direct competition with RKN for infection sites and space, alteration of the composition of root exudates, or through activation of plant defense reactions and other mechanisms (Smith et al 1986;Azcón-Aguilar and Barea 1996;Harrier and Watson 2004;Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since AM fungi and RKN are all indigenous soil organisms and therefore co-exist in plant roots, the potential role of AM fungi as biocontrol agents and their protective effects on plants against RKN have been well documented Diedhiou et al 2003). Studies have shown that inoculation with AM fungi can significantly reduce RKN infestation and reproduction in some plant-nematode systems (Hol and Cook 2005) such as papaya with Meloidogyne incognita (Jaizme- Vega et al 2006), olive planting stocks with M. incognita and Meloidogyne javanica (Castillo et al 2006), tomato with M. incognita (Talavera et al 2001;Siddiqui and Akhtar 2007), pyrethrum with Meloidogyne hapla (Waceke et al 2001), Prunus rootstocks with M. javanica (Calvet et al 2001), and banana with M. javanica (Rodriguez and JaizmeVega 2005). In addition to enhancement of plant nutrition, especially P nutrition, establishment of arbuscular mycorrhizae may exert beneficial effects on plant growth though direct competition with RKN for infection sites and space, alteration of the composition of root exudates, or through activation of plant defense reactions and other mechanisms (Smith et al 1986;Azcón-Aguilar and Barea 1996;Harrier and Watson 2004;Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the role of AMF in plant growth stimulation and protection (Pinochet et al, 1996;Calvet et al, 2001;Hernández-Dorrego, 2002;Sorensen et al, 2005;Jaizme-Vega et al, 2006;Barea et al, 2008), the objective of this work was to test the effect of twenty-five commercial fungicides which are among the most active chemicals currently applied in horticultural crops on the mycorrhizal symbiosis established by Glomus intraradices and Glomus mosseae isolates from commercial inocula, in leek (Allium porrum L.) seedlings under controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…De otro lado, la incorporación de micorrizas aumenta el crecimiento y favorece muchos cambios a nivel morfológico en el sistema radicular, estimulando la proliferación de raíces, lo que hace que las plantas sean más tolerantes al ataque de los nematodos 16,29,30 . En cuanto al porcentaje de colonización por HMA, existieron diferencias altamente significativas entre tratamientos.…”
Section: Resultsunclassified
“…En los últimos años se ha encontrado que cuando se inoculan las raíces de las plantas con hongos micorrizo arbusculares (HMA), se disminuye significativamente la incidencia de nematodos patógenos 14 . Existen ejemplos en especies frutales como el kiwi 15 , papaya 16 , y tomate 17 donde los HMA han disminuido el efecto negativo de los nematos patógenos. Debido a ésto, sería de gran utilidad conocer sí los HMA disminuyen estos efectos en plántulas de granadilla.…”
unclassified